Effect of CuO and ZnO Nano-Additives on the Tribological Performance of Paraffin Oil–Based Lithium Grease - Rawat S.S.; Harsha A.P.; Das S.; Deepak A.P. (My University, 2025)
The present study investigates the effect on the tribological behavior of paraffin grease incorporated with ZnO and CuO nanoparticles. ZnO nanoparticles of ∼32 nm were synthesized with a precipitation method. X-ray diffraction (XRD), Fourier transform infrared (FTIR), high-resolution scanning electron microscopy (HR-SEM), and energy-dispersive spectroscopy (EDS) were used to characterize the nanoparticles. The grease was formulated with lithium soap (lithium salt of 12-hydroxy stearate) and paraffin oil. The CuO and ZnO nano-additives were blended separately in the paraffin grease in the range between 0.2 to 1.0% w/w. The extreme pressure and antiwear behavior of the CuO and ZnO nano-additive-doped greases were evaluated as per ASTM D2596 and D 2266 respectively using a four-ball tester. Various physical properties of grease samples—for example, drop point, consistency, evaporation loss, water washout, and leakage tendency—were also examined as per ASTM D566, D1403, D1263, D1264, and D972, respectively. The antiwear test results showed that the maximum reduction in mean wear volume (MWV) was obtained (∼36 and ∼56%) with the incorporation of 0.2% w/w of CuO and ZnO nano-additives in the paraffin grease, respectively. At the same concentration, ∼31 and ∼28% decreases in energy consumption were also achieved by the dispersion of ZnO and CuO nano-additives in the paraffin grease. The worn surfaces of the test balls were studied with various analytical tools to determine the wear mechanisms. © 2019, © 2019 Society of Tribologists and Lubrication Engineers.